Sistem Pendukung Keputusan Penentuan Dosen Terfavorit Pilihan Mahasiswa Menggunakan Metode Simple Additive Weighting (SAW) - Frans’s Alfiando; Jordi Esa Putra; Muhammad Fiqran (Universitas Putra Indonesia YPTK Padang, 2021)
Lecturers are academic staff who are in charge of planning and implementing the learning process, guidance and training, and are able to bring students into activities held by the University, both official and non-official. Selection of favorite lecturers chosen by students can encourage lecturers to communicate more with students to be able to invite students to take part in groups or organizations involving students and lecturers. However, in reality, Universitas Putra Indonesia YPTK Padang is still not actively conducting this election. To overcome these problems, a Decision Support System was designed to determine the student's favorite lecturers by using the simple additive weighting method. The Decision Support System for Determining Favorite Lecturers of Student Choice is a system that is able to increase the ease of decision making in determining lecturers who have student attractiveness so that students are more active and more competent in the guidance of the selected lecturers. In this system the lecturer's assessment is based on 5 criteria. The criteria used are responsibility, discipline, attitude, initiative, and presence. To get the final conclusion as an alternative decision to determine the lecturer of this choice requires the calculation process stage on each variable that has been determined based on the criteria. The position of the decision support system in this study is as a decision supporter, not replacing the role of the decision maker, so that the decision maker has the right to fully refer to the decision support system or not. The research results from the calculated simple additive weighting method can be concluded that the favorite lecturer of the student's choice is lecturer 2 with a score of 1.00 which is the result of the highest ranking and can be used as an alternative for determining the favorite lecturer of the student's choice.